2005
DOI: 10.1093/intimm/dxh264
|View full text |Cite
|
Sign up to set email alerts
|

Association of SIGNR1 with TLR4–MD-2 enhances signal transduction by recognition of LPS in gram-negative bacteria

Abstract: SIGNR1, a member of a new family of mouse C-type lectins, is expressed at high levels in macrophages (Mphi) within the splenic marginal zone, lymph node medulla, and in some strains, in peritoneal cavity. We previously reported that SIGNR1 captures gram-negative bacteria, such as Escherichia coli and Salmonella typhimurium, as well as Candida albicans. We have now investigated the precise ligands and innate responses that involve SIGNR1. The interaction of SIGNR1 with FITC-dextran and E. coli was completely in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 44 publications
3
62
0
Order By: Relevance
“…Previous in vitro work has demonstrated that SIGN-R1 associates with the TLR4-MD2 complex on the plasma membrane and SIGN-R1 binds E. coli LPS, enhancing both TLR4 oligomerization and downstream signaling via IkB-a degradation (12). It was shown that anti-SIGN-R1 Ab treatment blocks cytokine production from pMfs (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous in vitro work has demonstrated that SIGN-R1 associates with the TLR4-MD2 complex on the plasma membrane and SIGN-R1 binds E. coli LPS, enhancing both TLR4 oligomerization and downstream signaling via IkB-a degradation (12). It was shown that anti-SIGN-R1 Ab treatment blocks cytokine production from pMfs (12).…”
Section: Discussionmentioning
confidence: 99%
“…Following binding of PAMPs by DC-SIGN, a signaling pathway is initiated that modulates TLR3-, 4-and -5-induced cytokine responses (9). Interestingly, a member of a family of DC-SIGN homologs described in mice, SIGN-related 1 (R1)/CD209b (10,11), has also been shown to interact with the TLR signaling system, with SIGN-R1 associating with the TLR4-MD2 complex to enhance signal transduction in response to LPS in Gram-negative bacteria in vitro (12). Unlike DC-SIGN, SIGN-R1 is not expressed on DCs but is on splenic marginal zone, lymph node, and peritoneal macrophages (pMfs) (13)(14)(15) and can recognize glycans from different pathogens (16).…”
mentioning
confidence: 99%
“…HEK293T cells, the mouse monocytic cell line RAW264.7 cells and RAW-transfectants (RAW-SIGNR1, RAW-control and RAW-SIGNR1Dcyto cells) were maintained as described previously [26]. Expression levels of SIGNR1 and Dectin-1 of these transfectants were analyzed with biotinylated anti-SIGNR1 clone 22D1 [28] with PE-streptavidine and anti-Dectin-1 clone 2A11 (AbD Serotec, Oxford, UK) with PE-anti-rat IgG, respectively.…”
Section: Cells and Microbesmentioning
confidence: 99%
“…SIGNR1 recognizes not only various polysaccharides, such as dextran and mannan, but also lipopolysaccharides (LPS) from Gram-negative bacteria (E. coli and Salmonella typhimurium) [23]. The physical association of SIGNR1 with the TLR4-MD-2 complex on the cell surface accelerates TLR4 oligomerization upon recognition of the non-reductive end of LPS core on Gram-negative bacteria [26]. In addition, SIGNR1 on resident peritoneal macrophages (rpMf) and SIGNR1-transfected RAW264.7 cells recognizes zymosan and heat-killed (HK) C. albicans together with Dectin-1 [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Although the detailed signaling pathways triggered by OMLs are still unknown, it is possible that this activity is associated with both CLR and TLR signaling. It has been shown that SIGNR1 associates with TLR4 to capture gram-negative bacteria and facilitate signal transduction to activate innate immune responses (47). CD8 + cells isolated from stimulated spleen cells of OML/OVA-treated mice showed cytotoxicity against E.G7-OVA tumor cells (OVA-transfected EL4 cells), which present OVA peptide as a model tumor antigen on MHC class I, but not against parental EL4 tumor cells (15).…”
Section: E Involvement Of C-type Lectin Receptors (Clrs) In Oml Uptamentioning
confidence: 99%